Phytochemical analysis of lichen (parmotrema praesoraediosum) and its antibacterial activity / Nur Alya Abdul Razak - Abdul Razak, Nur Alya (2017)
This study was done in order to analyze the phytochemical components and to investigate the antibacterial activity of a macrolichen, Parmotrema praesorediosum. The sample was extracted using cold extraction method with different polarity of solvents such as hexane, acetone and methanol. The analysis of phytoconstituent in hexane extract, acetone extract and methanol extract were determined through foam test, ferric chloride test, lead acetate test and test for alkaloid. The antibacterial activity of the crude extracts was tested against four microorganisms using the disk-diffusion method. The acetone extract showed the presence of alkaloid, flavonoid, saponin and phenolic compounds. Meanwhile, the methanol extract gave positive results only on the alkaloid, flavonoid and phenolic tests. However, there is no significant phytoconstituent available in the hexane extract. As regard to the antibacterial activity of the samples, we found that, the acetone extract showed a good inhibition against E.coli, B.subtilis and S.aureus. The result revealed that the macrolichen, P. praesorediosum has a future potential as antibacterial agent.